A Comprehensive Critical Analysis of Upanaha Sweda Along with its Mode of Action. - shree, Bhagya; Katti, Anand (International Research Journal of Ayurveda & Yoga, 2024)
Swedana is standard therapeutic procedure in Ayurvedic science which is intended to relieve stiffness, heaviness, coldness of the body part and induce perspiration which can be used as Poorva, Pradhana and Paschat Karma according to the need. Upanaha is one such procedure usually used as Ekanga sweda characterised by application of medicinal paste over affected part of body with or without heating, covering it with thick leather material as bandaging. It is considered as Vatahara, can be used in vatavyadhi with stiffness, contracture and pain predominant. Transdermal drug delivery system depends upon multiple factors and their combined effect in Upanaha sweda like prevention of heat loss, to increase effective absorption of active ingredients, self-fermentation process and presence of solubility enhancer causes the treatment effective. Main intention of this procedure is to provide contact of medicine with body part for long hours so has to provide effective swedana action and to bring its anti-inflammatory and analgesics effect to act upon body for long duration. By considering present day busy lifestyle of patient, many modifications can be made into this process. This article compiles all the literature available on upanaha, analyses it and presents with a temporal sequence to clarify all the nuances related to upanaha sweda.